Average Rank and Adjusted Rank Are Better Measures of College Student Success than GPA. Issue 4 (1st August 2022) - Wittman, Donald
Abstract: I show that there are better measures of student college performance than grade point average (GPA) by undertaking a fine‐grained empirical investigation of grading within a large public university. The value of using GPA as a measure of comparative performance is undermined by academically weaker students taking courses where the grading is more generous. In fact, college courses composed of weaker performing students (whether measured by their relative performance in other classes, SAT scores, or high school GPA) have higher average grades. To partially correct for idiosyncratic grading across classes, alternative measures, student class rank and the student's average class rank, are introduced. In comparison to a student's lower‐division grade, the student's lower‐division rank is a better predictor of the student's grade in the upper‐division course. Course rank and course grade are adjusted to account for different levels of academic competitiveness across courses (more precisely, student fixed‐effects are derived). SAT scores and high school GPA are then used to predict college performance. Higher explained variation ( R 2 ) is obtained when the dependent variable is average class rank rather than GPA. Still higher explained variation occurs when the dependent variable is adjusted rank.